PERAN OJK DALAM MELINDUNGI PEMEGANG MEDIUM TERM NOTES MELALUI PENERBITAN POJK NOMOR 30 TAHUN 2019 - Herry Christian, Jordy; Edenela, Kirana (Kertha Semaya : Journal Ilmu Hukum; Vol 8 No 9 (2020)DO - 10.24843/KS.2020.v08.i09.p02, 2020)
Tulisan ini mengkaji mengenai peran OJK dalam melindungi pemegang Medium Term Notes melalui penerbitan Peraturan OJK Nomor 30 Tahun 2019 dengan menggunakan pendekatan penelitian yuridis normatif. Hal yang akan dikaji adalah latar belakang OJK menerbitkan Peraturan OJK Nomor 30 Tahun 2019 yang mengatur mengenai efek bersifat utang dan/atau sukuk tanpa penawaran umum, yang salah satu contoh bentuknya adalah Medium Term Notes. Selain itu melalui tulisan ini, penulis juga akan mengkaji perbedaan pengaturan Medium Term Notes setelah ditetapkannya Peraturan OJK Nomor 30 Tahun 2019. Setelah mengkaji menggunakan pendekatan terhadap peraturan terkait, diketahui bahwa penetapan Peraturan OJK Nomor 30 Tahun 2019 adalah sebagai payung hukum guna mewujudkan kepastian hukum bagi pemegang Medium Term Notes untuk meminimalisir kasus gagal bayar seperti yang terjadi di SNP Finance. Perbedaan pengaturan penerbitan Medium Term Notes melalui POJK Nomor 30 Tahun 2019 secara jelas terlihat melalui hadirnya OJK dalam kewajiban pelaporan penerbitan Medium Term Notes dan adanya kewajiban pemeringkatan yang dilakukan oleh penerbit Medium Term Notes. Selain itu hadirnya peran Penata Laksana Penerbitan dan Agen Pemantau memberi dampak positif dalam mewujudkan asas keterbukaan guna realisasi dari Good Corporate Governance Principle.   This paper examines the role of Financial Fervices Authority in protecting Medium Term Notes holders through the issuance of Financial Fervices Authority Regulation No. 30 of 2019 using a normative juridical research approach. The matter to be examined is the background of Financial Fervices Authority issuing Financial Fervices Authority Regulation Number 30 of 2019 which regulates debt and/or sukuk securities without through public offering, one of the examples is Medium Term Notes. In addition, through this paper, the author will also examine differences in the regulation of the Medium Term Notes after the stipulation of Financial Fervices Authority Regulation Number 30 Year 2019. After examining using the approach to related regulations, it is known that the stipulation of Financial Fervices Authority Regulation Number 30 Year 2019 is as a legal umbrella in order to realize legal certainty for holders of Medium Term Notes to minimize default cases like SNP Finance. The difference in the arrangement of the issuance of the Medium Term Notes through Financial Fervices Authority Regulation Number 30 of 2019 is clearly seen through the presence of the Financial Fervices Authority in the reporting obligations of the issuance of the Medium Term Notes and the existence of the rating obligation performed by the issuer of Medium Term Notes. Besides that, the presence of the role of the Publishing Management and Monitoring Agent has a positive impact in realizing the principle of openness for the realization of the Good Corporate Governance Principle.